PEMBUATAN PUPUK ORGANIK CAIR MENGGUNAKAN TEKNOLOGI KOMPOSTING SEDERHANA - Kasmawan, I.G.A.; Sutapa, G.N.; Yuliara, I.M. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana MengabdiDO - 10.24843/BUM.2018.v17.i01.p18, 2018)
Plants in growth and development require two types of nutrients, namely macro and micro nutrients. However, only N, P, and K elements are needed plants for larger amount. The purpose of this research is to provide liquid organic fertilizer as balancing fertilizer considering the increasing price of fertilizer in the market. Research on the use of simple composting technology in the manufacture of liquid organic fertilizer is done by involving participants from the elderly group, which is light and can be done alone. The composter used is a 25 L gallon with an outer connecting hose. The end of the hose is immersed in a bottle of water to ensure the sustainability of the composting process in an anaerobic atmosphere. Production of liquid organic fertilizer using main ingredient in the form of foliage (5 kg) and livestock waste (1kg), with additives suchshrimp paste (100 g) and brown sugar (200 g), and 200 mL EM4 as bioactivator. Five successful liquid organic fertilizer products have the highest nitrogen (N), phosphorus (P), and potassium (K) content of 0.16%, 153,75 mg/L and 663,98 mg/L, respectively.